The Cyclic Peptide Cyclo-zp80r Controls Salmonella enterica and Listeria monocytogenes Replication in Non-Concentrated (NFC) Orange Juice: Antibacterial Effects and Mechanisms of Action - Zhouxia Wang; Ping Zeng; Jinhui Lu; Sharon Shui Yee Leung; Lanhua Yi (Foods, 2025)
The market for non-concentrated (NFC) orange juice is increasing rapidly due to consumer demand for nutrients and flavor. However, it encounters challenges in microbial safety, particularly from Salmonella enterica and Listeria monocytogenes. This study aimed to exploit a bio-preservative for NFC orange juice. Results showed that the cyclic peptide cyclo-zp80r had good antibacterial activity, with minimum inhibitory concentration values of 2–8 μM against S. enterica and L. monocytogenes. It exhibited bactericidal action against S. enterica and bacteriostatic action against L. monocytogenes at a concentration of 128 μM. This study explored the effect of cyclo-zp80r on the pathogenicity of S. enterica and L. monocytogenes. The mortality rate of Galleria mellonella exposed to these pathogens in NFC orange juice decreased from 100% to 60% after cyclo-zp80r treatment, surpassing the effectiveness of nisin. Cyclo-zp80r exhibited depolarization effects on S. enterica and L. monocytogenes. It increased outer membrane permeability and damaged the membrane structure of S. enterica. Cyclo-zp80r also caused distinct morphological changes, mainly cell collapse in S. enterica and localized bubble-like protrusions in L. monocytogenes. It induced reactive oxygen species production and DNA binding. The species diversity and abundance in NFC orange juice were also reduced by cyclo-zp80r, particularly in the genera Pantoea, Aeromonas, Pseudomonas, and Erwinia. Additionally, cyclo-zp80r exhibited excellent stability at high temperature (121 °C, 5 min) and in fresh orange juice. These results suggest that cyclo-zp80r could be developed as an effective food bio-preservative.